1995
DOI: 10.1002/neu.480280405
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor‐α induces substance P in sympathetic ganglia through sequential induction of interleukin‐1 and leukemia inhibitory factor

Abstract: The present study establishes that tumor necrosis factor-alpha (TNF-alpha) induction of sympathetic substance P (SP) requires sequential induction of both interleukin (IL-1) and leukemia inhibitory factor (LIF). TNF-alpha dose-dependently induces SP, an induction that is secondary to an increase in the SP precursor, preprotachykinin (PPT), mRNA. Since TNF-alpha conditioned medium (CM) mimics the effect of TNF-alpha by raising SP, actions that are not antagonized by a neutralizing TNF-alpha antibody, TNF-alpha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 32 publications
0
19
0
1
Order By: Relevance
“…We conclude that TNFa from these satellite cells appears to induce these neurons to synthesize neuropeptides and inflammatory agents [18]. Indeed, TNFa induces substance P (SP) [7], which along with calcitonin gene-related peptide (CGRP), is well known to be associated with neuropathic pain in rats [9]. It has been reported that DRG neurons innervating rat facet joints are immunoreactive for SP and CGRP, and that the ratios of CGRP-IR in L1 and L2 DRG neurons were significantly higher than in L3, L4, and L5 DRG in a rat model of facet joint inflammation [16].…”
Section: Fg-labeled Drg Neurons Innervating Rat L5/6 Facet Jointsmentioning
confidence: 88%
“…We conclude that TNFa from these satellite cells appears to induce these neurons to synthesize neuropeptides and inflammatory agents [18]. Indeed, TNFa induces substance P (SP) [7], which along with calcitonin gene-related peptide (CGRP), is well known to be associated with neuropathic pain in rats [9]. It has been reported that DRG neurons innervating rat facet joints are immunoreactive for SP and CGRP, and that the ratios of CGRP-IR in L1 and L2 DRG neurons were significantly higher than in L3, L4, and L5 DRG in a rat model of facet joint inflammation [16].…”
Section: Fg-labeled Drg Neurons Innervating Rat L5/6 Facet Jointsmentioning
confidence: 88%
“…In fact, TNF␣ is known to induce the release of SP and CGRP from peripheral terminals (Ding et al, 1995;Hua et al, 1996). Recombinant TNF␣ excites nociceptors and enhances heat-evoked release of CGRP from peripheral nerve terminals (Opree and Kress, 2000).…”
Section: Expression Of Tnfr 1 Mrna But Not Of Tnfr2 Mrna In Drg Neuronsmentioning
confidence: 99%
“…Wenn primär afferente Neurone über längere Zeit mit IL-1β behandelt werden, wird die Freisetzung von Substanz P über das COX-2-System bewirkt [51]. TNF induziert Substanz P in sympathischen Ganglien über die Induktion von IL-1 und leukemia inhibiting factor (LIF) [28]. IL-6 und LIF bewirken eine verstärkte Synthese von Galanin in sensiblen Neuronen [123].…”
Section: üBer Welche Wege Können Zytokine Bei Nervenläsionen Schmerz unclassified